Total serum bilirubin is an independent risk factor for coronary artery disease in men compared to women. Issue 6 (1st December 2016) - Nguyen, Anke; Adams, Heath; Gin, Julian; Yap, Natalie; Wilson-O'brien, Amy; Garlick, John; Wilson, Andrew M.
Abstract : Objective An elevated total serum bilirubin level has been demonstrated to be protective against cardiovascular disease with the majority of evidence limited to males. We assessed the hypothesis that total bilirubin is an independent risk factor for the presence of coronary artery disease (CAD) in men compared to women in high-risk patients. Methods and results Analysis was performed on 563 men and 249 women presenting for coronary angiography at our institution between October 2009 and March 2014. CAD was defined by 50% stenosis or more in the left anterior descending artery, left circumflex artery or right coronary artery. CAD was present in 78% of men and 55% of women. In males, patients with CAD had lower median total serum bilirubin levels compared to patients without CAD (12 vs 13 μ mol/L, P = 0.002). There was no difference seen in the female population (10 vs 10 μ mol/L, P = 0.344). On multivariate logistic regression, total serum bilirubin was an independent risk factor of CAD in the males (OR 0.96; 95% CI 0.93-0.99; P = 0.018) but not in females (OR 1.00; 95% CI 0.93-1.08; P = 0.908). Conclusion Total serum bilirubin is an independent risk factor for angiographically defined CAD in men and not in women. Serum bilirubin is readily available and inexpensive and may be a biomarker in addition to recognised cardiovascular risk factors.